2019
DOI: 10.25159/1998-8125/6059
|View full text |Cite
|
Sign up to set email alerts
|

Work-life balance, job satisfaction and turnover intention amongst information technology employees

Abstract: Talent retention is of particular concern in the information technology (IT) sector owing to globalisation, the skills shortage and rapidly advancing technology. Employee turnover has significant costs and negative consequences for organisations. The objective of this study was to explore the association between employees’ experiences of work-life balance (as measured by the Survey Work-Home Interaction- Nijmegen), job satisfaction (as measured by the Minnesota Satisfaction Questionnaire) and their turnover in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 144 publications
10
73
3
6
Order By: Relevance
“…Most behavioral studies which examine the relationship between job satisfaction and turnover intention found a significant and negative correlation. Oosthuizen et. al.…”
Section: The Relationship Between Work Stress Job Satisfaction and Tmentioning
confidence: 99%
“…Most behavioral studies which examine the relationship between job satisfaction and turnover intention found a significant and negative correlation. Oosthuizen et. al.…”
Section: The Relationship Between Work Stress Job Satisfaction and Tmentioning
confidence: 99%
“…Others suggested that job satisfaction and job commitment are supported by position recognition, organisational support, leadership attainment and task versatility among creative employees (Reid, Riemenschneider, Allen, & Armstrong, 2008). Oosthuizen, Coetzee and Munro (2019) proposed that the turnover rate is relatively high in the creative industry and that talent retention is significantly related to job satisfaction in such circumstances. In addition to having greater job satisfaction compared to those with managerial career orientation, these creative talents have a positive synergy effect on other personnel (McMurtrey Grover, Teng, & Lightner, 2002).…”
Section: Job Satisfaction In Creative Industriesmentioning
confidence: 99%
“…In addition, one of the most important reasons why people leave their jobs is job dissatisfaction (Oosthuizen et. Al., 2016).…”
Section: Issn: 2254-6235mentioning
confidence: 99%
“…On the other hand, dissatisfied workers tend to leave jobs, leading to high job turnover (Oosthuizen, et al, 2016). Turnover is a reality that concerns organizations, especially those that show high rates.…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation